The Study of Relationship Between FDI and Stock Market and The Real Estate Sector - Niharika Mehta (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The diversity and complexity of Property Market, its linkages with economy and investment sphere has necessitated a closer study on its dynamics and movement. This paper seeks to identify the position and the need for securitization of real estate in a multi-asset portfolio in order to be invested in Indian circumstances. The Johansen cointegration test for HPI (Real Estate Index) and NSE 50 (Stock market index) shows that there is no longer, nor is there any short-term, connection between those market types in the VAR exogenity component on quarterly data (Q 2009-10 to Q3 2016-2017). The division between the equity market and the immobilised market should then be kept within a fund for purposes of diversification. The desired class of assets for investment is shown by descriptive statistics. It also shows that direct investment in real estate is necessary to be classified as an asset class and that securitisation cannot be used to standardise the assets classes. Findings are relevant both for regulators and market traders. This research helps the alternate literature on investing in emerging markets..